2015
DOI: 10.1037/gdn0000019
|View full text |Cite
|
Sign up to set email alerts
|

Team identification and postdisaster social well-being: The mediating role of social support.

Abstract: Team identification and postdisaster social well-being: The mediating role of social support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 59 publications
(143 reference statements)
4
59
0
Order By: Relevance
“…This idea is consistent with previous studies which have applied social identity theory to explain sports fans' identification with their team, noting a range of antecedent motivations and psychological, physiological and sociological outcomes (Greenwood et al, 2006;Katz & Heere, 2013;Lock & Funk, 2016;Spaaij & Anderson, 2010;Tyler, 2013;Wann, 2006). Specifically, team identification has been associated with a need for geographically, ethnically and socially defined community groups to come together in times of adversity (Inoue, Funk, Wann, Yoshida, & Nakazawa, 2015), to express their national pride and cultural identity (Bernache-Assollant, Bouchet, Auvergne, & Lacassagne, 2011), providing psychological relief from feelings of depression and alienation, whilst promoting feelings of belonging and self-worth (Branscombe & Wann, 1991).…”
Section: Team Identificationsupporting
confidence: 88%
“…This idea is consistent with previous studies which have applied social identity theory to explain sports fans' identification with their team, noting a range of antecedent motivations and psychological, physiological and sociological outcomes (Greenwood et al, 2006;Katz & Heere, 2013;Lock & Funk, 2016;Spaaij & Anderson, 2010;Tyler, 2013;Wann, 2006). Specifically, team identification has been associated with a need for geographically, ethnically and socially defined community groups to come together in times of adversity (Inoue, Funk, Wann, Yoshida, & Nakazawa, 2015), to express their national pride and cultural identity (Bernache-Assollant, Bouchet, Auvergne, & Lacassagne, 2011), providing psychological relief from feelings of depression and alienation, whilst promoting feelings of belonging and self-worth (Branscombe & Wann, 1991).…”
Section: Team Identificationsupporting
confidence: 88%
“…In sum, the SIA posits that group identification increases the availability and quality of emotional support from in-group members. In line with this proposition, evidence indicates that developing a high level of team identification can facilitate the exchange of helping behaviors among fans of the team and increase the perceived quality of emotional support (Inoue, Funk, Wann, Yoshida, & Nakazawa, 2015;Inoue, Sato, Filo, Du, & Funk, 2017;Levine, Prosser, Evans, & Reicher, 2005). Importantly, the effect of team identification on perceived emotional support may exist regardless of whether or not a person attends games (Inoue et al, 2017;Wann et al, 2008).…”
Section: Team Identification and Emotional Supportmentioning
confidence: 79%
“…First, people could increase their subjective well-being by Spectatorship and Life Satisfaction 4 behaviorally engaging in sport events as spectators (Pawlowski et al, 2014). Second, people could maintain and enhance their well-being by psychologically engaging in sport events through social identification with teams competing in the events (Inoue, Funk, Wann, Yoshida, & Nakazawa, 2015).…”
Section: Spectatorship and Life Satisfaction 3 Sport Spectatorship Anmentioning
confidence: 99%
“…Regarding the psychological pathway, the relationship between team identification (i.e., social identification with a sport team) and subjective well-being can be predicted based on social identity theory (SIT; Tajfel & Turner, 1979). Research has shown that team identification is associated with social well-being, a collective and public evaluation of life functioning measured by collective self-esteem, social life satisfaction, or community cohesion (Inoue, Funk, et al, 2015). However, evidence of the positive relationship between team identification and Spectatorship and Life Satisfaction 5 subjective well-being-a more personal and private evaluation of one's own life (Keyes & Lopez, 2001)-is inconclusive, with a review of empirical studies suggesting that team identification could have an adverse effect (Inoue, Berg, & Chelladurai, 2015;Vallerand et al, 2008).…”
Section: Spectatorship and Life Satisfaction 3 Sport Spectatorship Anmentioning
confidence: 99%